C-Reactive Protein as an Early Predictor of Anastomosis Leakage after Colorectal Surgery: A Literature Review - Permana, Lucky; Syaiful, Ridho A (UI Scholars Hub, 2024)
Introduction. Anastomosis leakage is a defect in the intestinal wall at the anastomosis site after surgery. This condition is a serious complication causing increased morbidity and mortality. CRP is commonly used as an acute postoperative indicator after abdominal surgery. The use of CRP as an early predictor of anastomosis leakage after colorectal surgery is supported by several studies showing its good diagnostic value. However, using CRP as a biomarker is not standard at Cipto Mangunkusumo National Hospital. Therefore, this literature review aims to support the evidence for CRP in the early detection of anastomosis leakage after colorectal surgery. Method. This study is a literature review conducted by searching online databases, including PubMed, ScienceDirect, and ClinicalKey. Several key terms, such as